The principle of justice and the image of the nursing profession in society: A concept analysis - Mufimah, Mufimah; Kamaludin, Ridlwan (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The ethical principle of justice in nursing is often interpreted differently by patients and nurses. This principle does not function in isolation but rather complements other ethical values, leading to challenges in various situations. A common issue is the public perception of discrimination against patients utilizing the National Health Insurance, which affects the nursing profession’s image. Purpose: To establish a clear definition of the principle of justice in relation to the public perception of the nursing profession. Method: A concept analysis approach based on Avant’s framework was employed, utilizing online databases (PubMed and Google Scholar) with the keywords ‘justice,’ ‘professional image,’ and ‘nurse.’ Literature published between 2003 and 2023 was reviewed. Results: The concept analysis identified a conceptual and operational definition of justice concerning the nursing profession’s image. The study outlined the attributes, antecedents, consequences, and empirical indicators associated with nurses’ professional image. Conclusion: The operational definition of the nursing profession’s image in society refers to the public’s perception of the overall impression of nurses' behavior, which is deliberately shaped.